PENGARUH KONVERGENSI IFRS DAN UKURAN PERUSAHAAN TERHADAP TINGKAT KONSERVATISME AKUNTANSI (Studi Empiris Perusahaan Manufaktur yang terdaftar di BEI periode 2010-2013) - Samuel, Samuel; Juliarto, Agung (JURNAL AKUNTANSI DAN AUDITING, 2015)
The objective of this research is to analyze the influence of IFRS and firm size on the level of Accounting Conservatism. Measurement of Conservatism utilizes c-score based on Chi and Liu research (2009). This research refers to research conducted by Nugroho and Indriana (2012) with some modification. Population of this research were manufacturing companies that listed in Indonesian Stock Exchange (IDX) during 2010-2013. Data were collected by using purposive sampling method. A total data of 404 observations were analyzed. Multiple linear regression analysis was used as a main analysis tool. The results of this research show that IFRS significantly influence the level of Accounting Conservatism and firm size have no significant effect on the level of Accounting Conservatism. Whereas, control variables in this research show that profitability significantly influence the level of Accounting Conservatism and leverage have no significantly effect on the level of Accounting Conservatism.